Leader-member exchange and employees with disabilities’ job embeddedness: mediating effects of organizational climate - Hasnizawati Hashim; Sharifah Zannierah Syed Marzuki; Fazreena Mansor (Penerbit Universiti Kebangsaan Malaysia, 2023)
Given the lack of research on employees with disability embeddedness in organizations, this study aims to investigate the mediating effects of organizational climate between leader-member exchanges and employees with disabilities’ job embeddedness. A survey involving 282 employees with disability working in public and private Malaysia sectors was performed to test the study hypotheses. Furthermore, the study results were analysed using the structural equation modelling (SEM) AMOS mediation analysis and indicated partial mediating effects between the leader-member exchange, organizational climate, and employees with disabilities’s job embeddedness. As individuals with disability possessed different aptitudes that necessitated diverse management initiatives from supervisors, the reciprocal advantages gained from employee with disability-supervisor relationships and organizational climates should be duly considered. The consideration proved essential in influencing employees with disabilities’ work experiences and employee retention in organizations. It is hoped that these findings will enhance supervisors’ understanding on the impact of leader-member exchange as well as organizational climate in strengthening a high-quality relationship with the employees with disability which simultaneously will boost their job embeddedness.